Development of Mononuclear (Arene) Ruthenium Complexes as Anticancer Agents: A Review - Thilini U. Amarasinghe; Sarath D. Perera (The Open University of Sri Lanka, 2022)
(Arene)ruthenium complexes have displayed promising activity against cancer and showed fewer side effects compared to platinum-based drugs. Activity tuning of arene complexes have been explored by varying, amines, phosphines and other N^N, N^O, N^S, N^C, S^O chelating ligands. (Arene)Ru(II) complexes of the type [(η6-arene)Ru(X)(Y)(Z)], [(η6-arene)Ru(L)(X)(Y)], [(η6- arene)Ru(L^L)X]Y and [(η6-arene)Ru(L^X)(Y)], where arene = cymene (C), benzene (B), toluene (T), hexamethylbenzene (H); L = amine, phosphine; L^L = en, diamine, diphosphine, (X^Y) = oxalate, (L^X) = acylacetonate; and (X), (Y) = halides, triflates etc. exhibit a high structural variety, and offer much potential in drug design. In this review, an overview of the progress in the field of mononuclear ruthenium complexes containing arenes and other co-ligands such as, PTA (1,3,5-triaza-7-phosphaadamantane), ethylenediamine (en), phosphines, thiosemicarbazone, acylthiourea and their bioactivity is presented.